Spatial features of dose–surface maps from deformably-registered plans correlate with late gastrointestinal complications. (26th April 2017) - Moulton, Calyn R; House, Michael J; Lye, Victoria; Tang, Colin I; Krawiec, Michele; Joseph, David J; Denham, James W; Ebert, Martin A
Abstract: This study investigates the associations between spatial distribution of dose to the rectal surface and observed gastrointestinal toxicities after deformably registering each phase of a combined external beam radiotherapy (EBRT)/high-dose-rate brachytherapy (HDRBT) prostate cancer treatment. The study contains data for 118 patients where the HDRBT CT was deformably-registered to the EBRT CT. The EBRT and registered HDRBT TG43 dose distributions in a reference 2 Gy/fraction were 3D-summed. Rectum dose–surface maps (DSMs) were obtained by virtually unfolding the rectum surface slice-by-slice. Associations with late peak gastrointestinal toxicities were investigated using voxel-wise DSM analysis as well as parameterised spatial patterns. The latter were obtained by thresholding DSMs from 1–80 Gy (increment = 1) and extracting inferior–superior extent, left–right extent, area, perimeter, compactness, circularity and ellipse fit parameters. Logistic regressions and Mann–Whitney U-tests were used to correlate features with toxicities. Rectal bleeding, stool frequency, diarrhoea and urgency/tenesmus were associated with greater lateral and/or longitudinal spread of the high doses near the anterior rectal surface. Rectal bleeding and stool frequency were also influenced by greater low-intermediate doses to the most inferior 20% of the rectum and greater low-intermediate-high doses to 40–80% of the rectum length respectively. Greater low-intermediate doses to the superior 20% and inferior 20% of the rectum length were associated with anorectal pain and urgency/tenesmus respectively. Diarrhoea, completeness of evacuation and proctitis were also related to greater low doses to the posterior side of the rectum. Spatial features for the intermediate-high dose regions such as area, perimeter, compactness, circularity, ellipse eccentricity and confinement to ellipse fits were strongly associated with toxicities other than anorectal pain. Consequently, toxicity is related to the shape of isodoses as well as dose coverage. The findings indicate spatial constraints on doses to certain sections of the rectum may be important for reducing toxicities and optimising dose.